Gut Microbiota Mediate Insecticide Resistance in the Diamondback Moth, Plutella xylostella (L.) - Xia, Xiaofeng; Sun, Botong; Gurr, Geoff M.; Vasseur, Liette; Xue, Minqian; You, Minsheng (Frontiers in Microbiology, 2018)
The development of insecticide resistance in insect pests is a worldwide concern and elucidating the underlying mechanisms is critical for effective crop protection. Recent studies have indicated potential links between insect gut microbiota and insecticide resistance and these may apply to the Diamondback moth, Plutella xylostella (L.), a globally and economically important pest of cruciferous crops. We isolated Enterococcus sp. (Firmicutes), Enterobacter sp. (Proteobacteria), and Serratia sp. (Proteobacteria) from the guts of P. xylostella and analyzed the effects on, and underlying mechanisms of insecticide resistance. Enterococcus sp. enhanced resistance to the widely used insecticide, chlorpyrifos, in P. xylostella, while in contrast, Serratia sp. decreased resistance and Enterobacter sp. and all strains of heat-killed bacteria had no effect. Importantly, the direct degradation of chlorpyrifos in vitro was consistent among the three strains of bacteria. We found that Enterococcus sp., vitamin C, and acetylsalicylic acid enhanced insecticide resistance in P. xylostella and had similar effects on expression of P. xylostella antimicrobial peptides. Expression of cecropin was down-regulated by the two compounds, while gloverin was up-regulated. Bacteria that were not associated with insecticide resistance induced contrasting gene expression profiles to Enterococcus sp. and the compounds. Our studies confirmed that gut bacteria play an important role in P. xylostella insecticide resistance, but the main mechanism is not direct detoxification of insecticides by gut bacteria. We also suggest that the influence of gut bacteria on insecticide resistance may depend on effects on the immune system. Our work advances understanding of the evolution of insecticide resistance in this key pest and highlights directions for research into insecticide resistance in other insect pest species.